2011
DOI: 10.1161/circoutcomes.110.957951
|View full text |Cite
|
Sign up to set email alerts
|

Landmark Analysis at the 25-Year Landmark Point

Abstract: Abstract-This statistical primer presents the landmark analysis method, exploring its appropriate use and interpretation while recognizing its limitations. This observational method is used for comparing time-to-event outcome between groups determined during study follow-up. The goal of the landmark method is to estimate in an unbiased way the time-to-event probabilities in each group conditional on the group membership of patients at a specific time point, the landmark time. The need that led to its developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
344
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(347 citation statements)
references
References 27 publications
3
344
0
Order By: Relevance
“…17 Nevertheless, with Landmark analysis, findings become observational because some confounders may not be accounted for, and early events may be omitted, thus rendering the analysis susceptible to time point-specific results and loss of power. 38 The risk of dependence on any lack of proportionality of hazards, however, was partly defused by additional Landmarking at 12 months and at 1 month of follow-up with consistent results with late benefit of TEVAR ( Figure IIA-IIC in the online-only Data Supplement).…”
Section: Limitationsmentioning
confidence: 75%
“…17 Nevertheless, with Landmark analysis, findings become observational because some confounders may not be accounted for, and early events may be omitted, thus rendering the analysis susceptible to time point-specific results and loss of power. 38 The risk of dependence on any lack of proportionality of hazards, however, was partly defused by additional Landmarking at 12 months and at 1 month of follow-up with consistent results with late benefit of TEVAR ( Figure IIA-IIC in the online-only Data Supplement).…”
Section: Limitationsmentioning
confidence: 75%
“…Also, landmark survival analysis was performed to separately analyze the early and late mortality outcomes across the 3 groups. 16 All reported P values are 2-sided, and the conventional hypoglycemic agents and/or insulin therapy initiated postoperatively. Oral glucose tolerance test or glycated hemoglobin level were obtained as necessary to confirm the diagnosis of new-onset DM.…”
Section: Discussionmentioning
confidence: 99%
“…Although not randomized, the comparison is reasonable given the similarity of the cohort demographics. It provides a relatively unbiased comparison of these otherwise similar groups 25 , although it uses specific time points for comparison and therefore has less statistical power than that of a standard log-rank test. Our results suggest that the effectiveness of extended-duration temozolomide with cis-retinoic acid provided in a provincial cancer centre is at least similar to the clinical trial efficacy observed with 6 months of temozolomide.…”
Section: Discussionmentioning
confidence: 99%
“…This test allowed us to compare the proportions of patients living and dead in each cohort, while controlling for the fact that the rate may change over time. This methodology effectively compares patients who might have been eligible for more than 6 cycles of temozolomide in the eortc/ncic study with the patients in our cohort who received it 25 . Multivariate Cox proportional hazards modelling was used to determine the effect of individual prognostic variables on survival.…”
Section: Outcomes and Statisticsmentioning
confidence: 99%